Merocytophagy is an integrin-stabilized macrophage response to microbes reliant on Syk signaling - Deobald, Kelly N.; Steele, Shaun P.; Dominguez, Sedelia R.; Whiles, Shannon; Kawula, Thomas (Frontiers in Immunology, 2025)
Macrophages and dendritic cells acquire bacteria and cytosolic content from other cells without killing the donor cell through a trogocytosis-associated process termed merocytophagy. While characteristics of this behavior have been partially identified, the mechanism and potential contribution to the response to infection are unclear. Here, we reveal that a wide range of distinct species of bacteria stimulate enhanced merocytophagy in macrophages through pattern recognition receptor (PRR). Further, we found that cell-to-cell transfer in response to Francisella tularensis infection occurs in a predominantly MyD88-independent manner, relying on spleen tyrosine kinase (Syk) activity. Syk signaling during this response also results in increased surface expression of cell-to-cell adhesion proteins integrin α4, integrin β1, ICAM-1 and CD44 at the site of merocytophagy transfer, and depleting these surface molecules impairs merocytophagic cell-to-cell transfer. Altogether, our data demonstrate that merocytophagy is a host response to infection facilitated by tight cell-to-cell binding which molecularly resembles an immunological synapse between macrophages.